Sustentabilidad y cooperativismo: una propuesta metodológica basada en un proyecto real - Cabaleiro Casal, Mª José; Fernández-feijóo Souto, Belén (REVESCO. Revista de Estudios Cooperativos, 2007)
The aim of this work is to describe the methodology and proposals of action designed for the phase of the rural development model integrated in an Interreg III-A project, carried out by Spanish and Portuguese entities in the period 2006-2007. The final objective of this European project is to offer proposals for the future to improve the current situation of economic and social deterioration of primarily the inland town lands of the Galician-Portuguese border area. After a brief review of the basic theory, we describe the methodology used in the elaboration of reports and maps of the area under study. From these a diagnosis is made which permits us to reach conclusions concerning the most adequate model of rural development to give an impulse to the economic and social growth of the area. All of this to be carried under the criteria of social responsibility and based a network of participating enterprises. L’objectif de ce travail est de montrer la méthodologie et la proposition de comportement dessinés pour l’une des phases d’un Projet Interreg III - À, réalisé le long de la période 2006-2007, par des organismes espagnols et portugais. La dernière finalité de ce projet européen est d’offrir une proposition d’avenir pour l’actuelle situation de détérioration économique et sociale des municipalités intérieures de la Galice – Portugal placée en face, l’aire d’intérêt prioritaire. Après une brève révision des fondements théoriques, un objectif décrit la méthodologie employée dans l’élaboration du Rapport et de Cartes de situation de l’aire pour, à partir de ceux-ci, réaliser un diagnostic qui permet d’énoncer la proposition de modèle de développement rural considéré plus approprié à l’impulsion économique et sociale de la zone, sous des critères de responsabilité sociale et articulé grâce à des entreprises de participation.